Optimal investment policy with fixed adjustment costs and complete irreversibility - Nicolas Roys (Centre for Microdata Methods and Practice (cemmap), 2007)
We develop and solve analytically an investment model with fixed adjust-ment costs and complete irreversibility that reproduces observed investment dynamics at the micro-level. We impose a minimal set of restrictions on technology and uncertainty. Most of the results duplicate or generalize earlier findings that have been established either by simulations or under contrefactual assumptions.
Keywords: C61; D21; E2; 330; Investment; Adjustment Costs; Irreversibility; Dynamic Programming; Investition; Anpassungskosten; Irreversibility of Investment; Dynamische Optimierung